2020
DOI: 10.1038/s41598-020-72223-z
|View full text |Cite
|
Sign up to set email alerts
|

Age as a decisive factor in general anaesthesia use in paediatric proton beam therapy

Abstract: Proton therapy for paediatric cancer patients is an effective treatment; however, young children have may have difficulties staying still during irradiation. This study investigated the indication of general anaesthesia in paediatric proton therapy. Background information and anaesthesia/treatment protocols were retrospectively extracted from the medical records of cancer patients under 15 years who underwent proton therapy at Southern TOHOKU General Hospital, Fukushima, Japan between April 2016 and December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
(28 reference statements)
0
6
1
Order By: Relevance
“…All of them used the intravenous approach. There are also no differences when comparing our rate of serious adverse effects with those obtained by Buschbaum 8 (0.07%) (p = .542, Fisher's exact test) and Shimazu 15 (0.35%) (p = .432, Fisher's exact test), who both used a combined intravenous and inhalation anesthetic approach. Table 2 summarizes the key data from the present study alongside the other studies identified in the evidence search that concentrate exclusively on anesthetic management in PT.…”
Section: Re Sultscontrasting
confidence: 45%
See 1 more Smart Citation
“…All of them used the intravenous approach. There are also no differences when comparing our rate of serious adverse effects with those obtained by Buschbaum 8 (0.07%) (p = .542, Fisher's exact test) and Shimazu 15 (0.35%) (p = .432, Fisher's exact test), who both used a combined intravenous and inhalation anesthetic approach. Table 2 summarizes the key data from the present study alongside the other studies identified in the evidence search that concentrate exclusively on anesthetic management in PT.…”
Section: Re Sultscontrasting
confidence: 45%
“…7 Furthermore, PT centers are often free-standing facilities without hospitals capable of providing advanced care nearby. 8 Although the available data show that total intravenous anesthesia or combined intravenous and inhalation anesthesia are commonly used, 6,[8][9][10][11][12][13][14][15][16][17] we believe that daily cannulation of a peripheral vein can become a challenging and painful experience, and that systematic access to a permanent central venous line may increase the risk of infectious complications, as these children are sometimes severely immunocompromised. 18 Our experience is that pediatric PT under inhalation anesthesia may be adequate, not time consuming, and safe, with a low rate of adverse effects, which is similar to that of other anesthetic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…This record of safety may be particularly important where the anesthesia is being administered at a remote location with the patient removed from the immediate reach of the primary provider. Second, the introduction of the laryngeal mask airway has provided a safe and less invasive method of airway management that avoids the morbidity associated with daily endotracheal intubations [14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Young children are often unable to cooperate with diagnostic imaging, minimally invasive procedures, and/or cancer treatments, many of which require them to remain motionless or endure discomfort. A child undergoing treatment of a brain tumor can thus require anesthesia at multiple time points in addition to their respective surgeries: (1) during their initial magnetic resonance imaging procedure and any subsequent surveillance imaging5; (2) for placement of indwelling venous catheters for the delivery of intensive chemotherapeutic drugs and; (3) for the planning and delivery of irradiation over several weeks 14,15. Anesthetic drugs are also administered in the intensive care unit (ICU) during periods of critical illness for which sedation may be necessary over days to weeks.…”
Section: Role Of Anesthetic Neurotoxicity In Long-term Outcomes Among...mentioning
confidence: 99%
“…A child undergoing treatment of a brain tumor can thus require anesthesia at multiple time points in addition to their respective surgeries: (1) during their initial magnetic resonance imaging procedure and any subsequent surveillance imaging 5 ; (2) for placement of indwelling venous catheters for the delivery of intensive chemotherapeutic drugs and; (3) for the planning and delivery of irradiation over several weeks. 14,15 Anesthetic drugs are also administered in the intensive care unit (ICU) during periods of critical illness for which sedation may be necessary over days to weeks. There exists little data on the frequency or duration of ICU sedation in the management of pediatric patients with posterior fossa tumors; however, it is noteworthy that the most common oncologic diagnosis associated with pediatric ICU utilization is a brain tumor.…”
Section: Role Of Anesthetic Neurotoxicity In Long-term Outcomes Among...mentioning
confidence: 99%